Age-dependent association of pulse wave velocity with coronary artery disease and myocardial aging in high-risk patients. Issue 4 (April 2019) - Georgiopoulos, Georgios; Papaioannou, Theodore G.; Magkas, Nikos; Laina, Ageliki; Mareti, Alexia; Georgiou, Stelios; Mavroeidis, Ioannis; Samouilidou, Elisa; Delialis, Dimitris; Tousoulis, Dimitris; Kanakakis, John; Stamatelopoulos, Kimon
Abstract : Aims: Progressive arterial stiffening, as a marker of arterial aging, may reach a plateau in elderly patients and may thus lose its clinical utility. This phenomenon may be more prominent in high-risk patients. We aimed to investigate if carotid-to-femoral pulse wave velocity (cf-PWV) is related to coronary artery disease (CAD) and diastolic dysfunction in elderly high-risk patients as compared to a control group of younger individuals. Methods: One-hundred and ninety-two high-risk stable patients who underwent coronary artery angiography and assessment of cf-PWV were consecutively recruited. Indices of diastolic dysfunction were also measured by echocardiography, including the volume of the left atrium and the ratio of early transmitral peak velocity (E) to the mitral annular early diastolic velocity (E'). Results: Increased cf-PWV was associated with the presence of CAD [odds ratio (OR) 1.34, P  = 0.02], number of diseased coronary vessels (OR 1.17, P  = 0.029) and CAD severity ( P  = 0.023) as assessed by Gensini score, in patients less than 65 years old after adjustment for traditional risk factors. Moreover, cf-PWV correlated with E/E' ( P  = 0.019) and increased the odds by 16% (OR 1.16, P  = 0.048) for more severe diastolic dysfunction in patients aged below 65 years old. None of these outcomes correlated with cf-PWV in the elderly. Conclusion: In high cardiovascular risk patients, an age-dependent association of cf-PWV with CAD and diastolic dysfunction was evinced. In contrast to younger patients, these results suggest that measuring arterial stiffness in elderly high-risk patients may lack clinical value.